Keanekaragaman Jamur dan Bakteri Rizosfer Bawang Merah terhadap Patogen Moler - Bayu Rahmad Bernadip; Hadiwiyono Hadiwiyono; Sudadi Sudadi (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2014)
TITLE : DIVERSITY OF FUNGI AND BACTERIA OF SHALLOT RIZOSPHERE AGAINST MOLER PATHOGEN. The diversity of microorganisms is important in maintaining soil environment equilibrium, include hindering plant pathogens as moler. Moler is a disease caused by Fusarium oxysporum f. sp. cepae (FOCe) that cause lost all the crops of shallot. Research is aimed to study the fungus and bacteria diversity of shallot rizosphere and their antagonism against FOCe which important to be biological agent of moler disease. The study was held in a descriptive explorative method, soil samples taken to know the relation of plant condition with fungus and bacteria diversity of shallot rhizosphere and their antagonism against FOCe. Fungus and bacteria were isolated from both of healthy and moler diseased of shallot rhizosphere. The result showed that healthy and moler diseased shallot rhizosphere had population of fungus and bacteria with no differences and had medium level of fungus and bacteria diversity. The fungus and bacteria isolated from healthy shallot rhizosphere had stronger antagonism against FOCe.